1971
DOI: 10.1128/aem.21.3.470-475.1971
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clostridium botulinum Toxigenic Types A, B, and E for Fatty and Carbohydrate Content 1

Abstract: Lyophilized, 48-hr log-phase vegetative cells were extracted with chloroformmethanol (2:1, v/v) and ethanol-ether (3:1, v/v) and then saponified with methanolic KOH. Gas-liquid chromatography of the methyl esters of extractable fatty acids revealed distinctive "pattern profiles" of Clostridium botulinum toxigenic types "A," "B," and "E." C. perfringens type "A" and Escherichia coli strain "B" were also studied in a similar manner and were found to give pattern profiles which were distinct even from those obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, in comparison with headspace GLC, the Microbial Identification System method was thought to be too complicated. Toxigenic types A, B, and E of C. botulinum were studied by Fugate et al (52). In contrast to the results of CFA analysis with toxigenic types of C. perfringens (112), those investigators suggested that quantitative analysis of the CFAs could serve to distinguish types of C. botulinum.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…However, in comparison with headspace GLC, the Microbial Identification System method was thought to be too complicated. Toxigenic types A, B, and E of C. botulinum were studied by Fugate et al (52). In contrast to the results of CFA analysis with toxigenic types of C. perfringens (112), those investigators suggested that quantitative analysis of the CFAs could serve to distinguish types of C. botulinum.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…Solomon et al (13) showed that C. botulinum type E shared common somatic antigens among the nonproteolytic strains of the organism. While non-peptidoglycan carbohydrate components of the cell wall of these strains were hexoses (glucose and galactose (3)) and hexosamine (glucosamine and galactosamine (5)), none of the antigens of these strains have yet been isolated, nor have their composition and antigenic specificity been elucidated.…”
Section: Galactosaminementioning
confidence: 99%